Model Spasial Deforestasi di KPHP Poigar, Provinsi Sulawesi Utara - Afandi Ahmad; Muhammad Buce Saleh; Teddy Rusolono (Jurnal Penelitian Kehutanan Wallacea, 2016)
Forest is a part of the ecosystem that provides environmental services. Deforestation may decrease forest function in an ecosystem. This study aims to build a spatial model of deforestation in a forest management unit (FMU) of Poigar. Deforestation analysis carried out by analyze the change of forest cover into non-forest cover with post classification comparison technique. Driving forces of deforestation carried out by spatial modeling using binary logistic regression models (LRM). Result of logistic regression model was used to predict the deforestation in 2013 and compare the prediction result with actual deforestation. The result showed that forest loss from the 2000 to 2013 period amounted 12,668.2 hectares. Deforestation in FMU of Poigar influenced by six factors there are distance from the road, distance from the settlement, distance from the river, population density, elevation and slope. Logistic regression model was built using five explanatory variables that are the distance from the road, distance from the river, population density, elevation and slope. Population density and accessibility is the most influented factor caused deforestation in FMU of Poigar. Prediction of deforestation could predict about 58 % of actual deforestation spatialy, so spatial models of deforestation could be an information to guidance on future management of FMU of Poigar.